English learner instruction through collaboration and inquiry in teacher education - Nagle, James F. (Emerald Publishing Limited : Information Age Publishing, Inc., 2014)
In an era of accountability and increased demand of literacy competency, this book provides examples of how teacher educators and teachers have come together to learn from each other and from English learners. The chapters in this book follow a teacher learning framework that highlights joint work, features inquiry into practice and integrates disciplinary content knowledge with culturally and linguistically responsive teaching.While the chapters feature different venues for teacher learning, they all depict the process of teachers and teacher educators striving to integrate English learner instruction into mainstream teacher education. This book will be a resource for faculty in teacher education programs and for administrative personnel in school districts to illustrate the process of building authentic collaborations that can improve teacher learning and understanding about English learner instruction.